👤

{[(3^2+4^2):5^2]^3-2^3-3^3}x3^2​

Răspuns :

Răspuns:    - 306

Explicație pas cu pas:

{[(3^2 + 4^2) : 5^2]^3 - 2^3 - 3^3} x 3^2 =

​{[(9 + 16) : 25]^3 - 8 - 27} x 9  

{[25 : 25]^3 - 35] x 9 =

{1^3 - 35 } x 9 =

- 34 x 9 =

- 306

Răspuns: [tex]\red{\bf -306~}[/tex]

Explicație pas cu pas:

[tex]\bf \bigg\{\Big[\big(3^{2}+ 4^{2}\big) : 5^{2}\Big]^{3} - 2^{3} - 3^{3} \bigg\} \cdot 3^{2} =[/tex]

[tex]\bf \bigg\{\Big[\big(9+ 16\big) : 5^{2}\Big]^{3} - 2^{3} - 3^{3} \bigg\} \cdot 3^{2} =[/tex]

[tex]\bf \bigg[\Big(\big 25 : 5^{2}\Big)^{3} - 2^{3} - 3^{3} \bigg] \cdot 3^{2} =[/tex]

[tex]\bf \bigg[\Big(\big 5^{2}: 5^{2}\Big)^{3} - 2^{3} - 3^{3} \bigg] \cdot 3^{2} =[/tex]

[tex]\bf \bigg[\Big(\big 5^{2-2}\Big)^{3} - 2^{3} - 3^{3} \bigg] \cdot 3^{2} =[/tex]

[tex]\bf \Big[\big( 5^{0}\big)^{3} - 8 - 27 \Big] \cdot 3^{2} =[/tex]

[tex]\bf \big(1^{3} - 35 \big) \cdot 3^{2} =[/tex]

[tex]\bf \big(1 - 35 \big) \cdot 9 =[/tex]

[tex]\bf \big(-34 \big) \cdot 9 =\red{\boxed{\bf -306~}}[/tex]